Multicenter Implementation of a Novel Management Protocol Increases the Outpatient Treatment of Pulmonary Embolism and Deep Vein Thrombosis. (29th November 2018) - Kabrhel, Christopher; Rosovsky, Rachel; Baugh, Christopher; Connors, Jean; White, Benjamin; Giordano, Nicholas; Torrey, Jasmine; Deadmon, Erin; Parry, Blair Alden; Hagan, Sean; Zheng, Hui
Abstract: Objective: The objective was to determine whether a protocol combining risk stratification, treatment with the direct‐acting oral anticoagulant rivaroxaban, and defined follow‐up is associated with a greater proportion of patients with venous thromboembolism (VTE) treated as outpatients, without hospital admission. Methods: We performed a multicenter study of patients diagnosed with VTE (pulmonary embolism [PE] or deep vein thrombosis [DVT]) in two urban EDs, 18 months before and 18 months after implementation of an outpatient VTE treatment protocol. Patients with radiographically confirmed acute VTE were eligible. Our primary outcome was the proportion of VTE patients discharged from the ED or observation unit (i.e., without hospital admission). We performed subgroup analyses according to hospital, DVT and PE, and low‐risk PE. We also assessed 7‐ and 30‐day mortality, major bleeding, and returns to the ED. We compared proportions using chi‐square and Fisher's exact tests. Results: We enrolled 2, 212 patients, 1, 081 (49%) before protocol and 1, 131 (51%) after protocol. Mean age (59 years vs. 60 years), female sex (49% vs. 49%), other demographics, comorbid illness, and PE risk stratification were similar before and after. After protocol, more VTE (35% from 26%, p < 0.001), PE (18% from 12%, p = 0.002), low‐risk PE (28% from 18%, p < 0.001), and DVT (60% from 49%, p = 0.002) patients were treated as outpatients. Mortality, bleeding, and returns to ED were rare and did not increase after protocol. Conclusions: A treatment protocol combining risk‐stratification, rivaroxaban treatment and defined follow‐up is associated with an increase in PE and DVT patients treated as outpatients, with no increase in adverse outcomes.